Pharmacological and non-pharmacological alternatives for the treatment of dental anxiety in pediatric patients in the dental clinic: literature review - León Valencia, Wilson Andrés (2024)
Odontophobia in pediatric patients, that is, the exacerbated fear of the environment and dental interventions, is regularly combated with non-pharmacological and non-pharmacological therapies. Aim. To determine the effectiveness of these two types of therapies to control dental anxiety in pediatric dental patients. Materials and methods. A narrative review of scientific literature published in online databases with dates between 2018 and 2022 was carried out; In addition, other inclusion or exclusion criteria were considered, obtaining a total of 25 articles that met the requirements. According to what was analyzed, it was determined that the most used non-pharmacological therapies are: music therapy, desensitization, the “say, show, do” technique and the positive reinforcement technique; while the most common pharmacological therapies are: nitrous oxide inhalation, intravenous sedation and oral administration of benzodiazepines. Results. For the authors of this study, within non-pharmacological techniques it is advisable to use the “say, show, do” technique, since fear of the unknown is usually a strong trigger for anxiety to occur; Desensitization can also be used, which provides relaxation resources. In both cases, medications are not required; However, in complex cases, pharmacological therapies are used, the choice of which must always be evaluated by the treating dentist to verify whether the patient is suitable, and in all cases the application of intravenous sedative drugs must be supervised by an anesthesiologist.